2018
DOI: 10.3892/ijmm.2018.3591
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic and prognostic values of contrast‑enhanced ultrasound combined with diffusion‑weighted magnetic resonance imaging in different subtypes of breast cancer

Abstract: The present study aimed to investigate the diagnostic and prognostic values of contrast-enhanced ultrasound (CEUS) combined with diffusion-weighted magnetic resonance imaging (DW-MRI) in different subtypes of breast cancer (BC). CEUS and DW-MRI were conducted in 232 patients with BC prior to surgical treatment. Patients were categorized as having the luminal A subtype, the luminal B subtype, triple-negative subtype or the human epidermal growth factor receptor 2 (Her-2)-positive subtype according to their expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…The TN subtype of BC has a higher histological grade and a worse prognosis compared with the other three subtypes, but its CEUS perfusion pattern lacks specificity and it may thus be confused with benign lesions. 39 The three cases of medullary carcinoma in this study were all TN subtype BCs. Previous studies found that the CEUS perfusion pattern of medullary carcinoma usually presents as regular morphology, with well-defined margins and homogenous enhancement.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The TN subtype of BC has a higher histological grade and a worse prognosis compared with the other three subtypes, but its CEUS perfusion pattern lacks specificity and it may thus be confused with benign lesions. 39 The three cases of medullary carcinoma in this study were all TN subtype BCs. Previous studies found that the CEUS perfusion pattern of medullary carcinoma usually presents as regular morphology, with well-defined margins and homogenous enhancement.…”
Section: Discussionmentioning
confidence: 87%
“…CEUS perfusion parameters were found to correlate with vascular endothelial growth factor (VEGF) expression and predictors of poor prognosis, 21 in addition, it can provide excellent predictive value for high‐grade malignancy of BC and might help to determine appropriate therapeutic strategies 22 . Although previous studies have explored the correlation between CEUS characteristics and certain histopathological features of BC, 23,24 few studies have focused on the identification of BC molecular subtypes based on CEUS characteristics 25,26 . The current study thus aimed to explore the correlation between qualitative and quantitative CEUS characteristics and the different pathological molecular subtypes of BC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The model's diagnostic accuracy was significantly better for patients >35 y, for maximum lesion diameter >20 mm, and for distance from the lesion's deep edge to the pectoralis major ≤3.05 mm. CEUS is a promising method for the accurate diagnosis of breast cancer and can optimize BI-RADS categorization (22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Ayrıca, luminal B grubundaki ADCmean değeri, HER2 pozitif gruba göre anlamlı olarak daha yüksek bildirilmiştir (p<0.05). HER2 pozitif ve triple negatif gruplarla karşılaştırıldığında, luminal A ve luminal B grupları anlamlı olarak daha yüksek ADCmin değerleri göstermiştir (18) . DW görüntülemenin tümörün biyolojisi ve mikrostrüktürel özelliklerini hakkında bilgi sağladığı bildirilmiştir.…”
Section: Tartişma Dw Mr'da Yüksek Manyetik Alan Gücüne Sahipunclassified